The Determinants of Capital Structure in SMEs: Evidence from the U.K. companies - SHI, YUEJUN (2017)
Compared with large enterprises, SMEs have their own characteristics, thus the capital structure theory is not fully applicable to SMEs. Therefore, this thesis puts forward the influencing factors of capital structure of SMEs by combining the capital structure theory and current situation of SMEs in the United Kingdom. The analysis of influencing factors is mainly based on the industry level and the company level. At the company level, this thesis analyzes the correlation between leverage ratio and profitability, scale of the company, growth opportunities, non-debt tax shields, asset structure, risk and liquidity. At the industry level, the difference between leverage across different industries is analyzed. In addition, panel data model is used to analyze the data of 466 UK-listed SMEs from 2008 to 2016. The results show that leverage is significantly positively associated with the scale of enterprises and asset structure, and is negatively associated with risk, profitability and liquidity. The further analysis of the industry factors of the sample companies find that the SMEs’ capital structure is sensitive to the changes in industry factors and there exists a significant variation across industries in the independent variables. The conclusion of this thesis is consistent with the pecking-order theory and partly confirms the view of trade-off theory and agency cost theory. Finally, we put forward corresponding policy suggestions to optimize the capital structure of SMEs. Thus this article explores the capital structure, which helps to understand the financing demand of the small companies, and is beneficial for the maximization of the value of SMEs.